1962
DOI: 10.1530/jrf.0.0030363
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Phosphomonoesterase Activities in the Seminal Plasmas of the Domestic Cock, Turkey Tom, Boar, Bull, Buck Rabbit and of Man

Abstract: Summary. A comparison of the phosphomonoesterase activity, against 4-nitrophenyl phosphate, in the seminal plasma of the domestic cock, turkey torn, boar, bull, buck rabbit and of man has been made. The acid-phosphatase(s) activity at pH 4-9 was highest in man, the cock and turkey torn, and lowest in the boar and rabbit, with the bull inter¬ mediate. Alkaline-phosphatase activity was highest in the boar and rabbit, lowest in the cock, turkey torn and in man, with the bull again intermediate. It is possible tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
3
19
1
Order By: Relevance
“…Several reports in the literature indicated that the level of phosphatases differs greatly between species (BELL and LAKE, 1962;MANN, 1964;and MURDOCH and WHITE, 1968). O u r finding that buffalo semen had almost 150 O/o and 250 O / o higher alkaline and acid phosphatase activity, respectively, than that of Friesian and native bulls agrees with the findings of ROY et al (1960).…”
Section: Discussionsupporting
confidence: 84%
“…Several reports in the literature indicated that the level of phosphatases differs greatly between species (BELL and LAKE, 1962;MANN, 1964;and MURDOCH and WHITE, 1968). O u r finding that buffalo semen had almost 150 O/o and 250 O / o higher alkaline and acid phosphatase activity, respectively, than that of Friesian and native bulls agrees with the findings of ROY et al (1960).…”
Section: Discussionsupporting
confidence: 84%
“…Material was obtained for staining from the caput flexure of the epididymis and the cauda epididymidis of four rabbits, six hamsters and six rats immediately after death, and ejaculated spermatozoa were collected from two rabbits by means of an artificial vagina (Walton, 1958 Every sample was washed three times in normal saline, centrifuging each time at low speed for about 2 min, in order to remove excess epididymal plasma which might itself contain alkaline phosphatase (Bell & Lake, 1962). The procedure was shown to be absolutely necessary in the golden hamster where the content of alkaline phosphatase in epididymal plasma was so high that, after staining, the spermatozoa were completely obscured on the slides as a result of a generalized reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of AP in the seminal plasma of the fowl is extremely high, and, when compared with that of several mammals, only human seminal plasma shows a higher activity (Bell & Lake, 1962). Since the greater part of the AP of fowl semen was present mainly in small particles in seminal plasma, and since it was difficult to be absolutely certain that washed spermatozoa were free from contamination with the particles, the amount of AP activity in the spermatozoa remains doubtful.…”
Section: Assay Of Enzymesmentioning
confidence: 97%